Farmers’ Perception of Critical Factors for Success of Indigenous Shrimp Feed in India - Ponnusamy*, K; Swathilakshmi, P S (Fishery Technology, 2025)
The success of shrimp farming depends on adoption of cost effective and environment friendly technologies including feed. A study was conducted in two districts of Andhra Pradesh and one district of Tamil Nadu to asses the pattern of shrimp feed usage among coastal farmers. The findings revealed that the most important criteria for a good feed as considered by farmers were faster growth followed by water stability, low cost and good odour. Most farmers broadcast the feed from the dyke of ponds in both the states whereas farmers in Tamil Nadu practice feeding from boat also. Majority of farmers do feed rationing based on the bio-estimation of stock in the pond in Andhra Pradesh. Two-third of farmers in Tamil Nadu were found to purchase feed every week from dealers while farmers of Andhra Pradesh purchase the same with gaps varying from one week to four weeks. The major constraints reported by farmers in feed management were poor stability and escalating feed cost. The cost of feed and higher growth performance were found to be the critical factors for adoption of indigenous shrimp feed on the basis of assessment using Rank Based Quotient method.